Respuesta :

Answer:

Part A. x+6y =6 means : 6y = - x+6

Part B. solution of the system  : y = (-1/6)x+1 ....(1)  

            y =  (1/3)x -2 ....(2)

Intersection = (6,0)

Part C. PartC : Algebraically  by (1) and (2) : (-1/6)x+1 =  (1/3)x -2

(-1/6)x  - (1/3)x = -2-1

(-x-2x)/6= -3

-3x = -18

so : x = 6  put this value in (1) or (2) : y = (-1/6)(6)+1 =0 the solution is : (6 ;0)

Part A Graph is down below.

Hope this helps you out! If not, let me know and add what you are wanting/needing! Good luck! ☺

-Karleif Jonsi-

Ver imagen Аноним
ACCESS MORE